ANALYSIS OF SPECIFIC FEATURES OF NEUROLOGY (Conference Zone, 2022)
In this article, the content of the field of neurology, which is one of the most important fields of medicine, and its history are given. In addition, the article focuses on the physiological features of neurology. General conclusions are drawn.